Light, Sound, and Melatonin: Investigating Multisensory Pathways for Visual Restoration - Dario Rusciano (Medicina)
Multisensory integration is fundamental for coherent perception and interaction with the environment. While cortical mechanisms of multisensory convergence are well studied, emerging evidence implicates specialized retinal ganglion cells—particularly melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs)—in crossmodal processing. This review explores how hierarchical brain networks (e.g., superior colliculus, parietal cortex) and ipRGCs jointly shape perception and behavior, focusing on their convergence in multisensory plasticity. We highlight ipRGCs as gatekeepers of environmental light cues. Their anatomical projections to multisensory areas like the superior colliculus are well established, although direct evidence for their role in human audiovisual integration remains limited. Through melanopsin signaling and subcortical projections, they may modulate downstream multisensory processing, potentially enhancing the salience of crossmodal inputs. A key theme is the spatiotemporal synergy between melanopsin and melatonin: melanopsin encodes light, while melatonin fine-tunes ipRGC activity and synaptic plasticity, potentially creating time-sensitive rehabilitation windows. However, direct evidence linking ipRGCs to audiovisual rehabilitation remains limited, with their role primarily inferred from anatomical and functional studies. Future implementations should prioritize quantitative optical metrics (e.g., melanopic irradiance, spectral composition) to standardize light-based interventions and enhance reproducibility. Nonetheless, we propose a translational framework combining multisensory stimuli (e.g., audiovisual cues) with circadian-timed melatonin to enhance recovery in visual disorders like hemianopia and spatial neglect. By bridging retinal biology with systems neuroscience, this review redefines the retina’s role in multisensory processing and offers novel, mechanistically grounded strategies for neurorehabilitation.